Analisis Penyebab Penunggakan Pajak Kendaraan Bermotor (PKB) Di Jepara - Subadriyah Subadriyah; Siska Alfiani (Jurnal Rekognisi Akuntansi, 2018)
This research was conducted at the Regional Revenue Service Unit (UPPD) office of Jepara Regency. This study was conducted to determine the variables of awareness, income, distance of residence, quality of service, negligence, education and understanding of taxes affect motor vehicle tax arrears. The analytical tool used is quantitative analysis. The sample in this study were motorized vehicle taxpayers registered at the Jepara Regency Revenue Service Unit (UPPD) office, totaling 100 respondents. The analytical method used is Multiple Linear Regression analysis. The sampling method used is simple random sampling. The results of this study indicate that based on statistical results the t value of the awareness variable has a negative effect. Income variable has a positive influence. The variable of residence distance has a negative effect, the variable of service quality has a negative influence. Negligence variable has a positive effect. The education variable has a negative effect. The tax understanding variable has a positive effect on Motor Vehicle Tax Arrears. Based on the f test, the variables of awareness, income, distance of residence, quality of service, negligence, education and understanding of taxes together affect the arrears of Motor Vehicle Tax.